Factor IX and Factor XI inhibition following cardiac surgery leading to massive transfusion. Issue 2 (21st July 2016) - Churchill, Sara; Al‐Meshhedani, Hasham; Percy, Charles; Thomas, Dafydd
Summary: This case report highlights the importance of accurate interpretation of haemostatic tests in patients who have undergone cardiac surgery requiring cardiopulmonary bypass. We report a case of major haemorrhage and massive transfusion where factor IX and factor XI inhibitors were present on formal coagulation testing giving a rotational thromboelastometry (ROTEM) result suggestive of an excessive heparin effect.